Advances on cancer vaccine trials registered in China and the USA in 2014-2024 - Shi, Wei; Chen, Zhuo; Yu, Qin; Zhang, Lingli (Frontiers in Oncology, 2025)
ObjectiveThe clinical trials of cancer vaccine in China and the USA were summarized and compared over the past decade, thus putting forward suggestions for future clinical development in this field.MethodsMainly based on the Centre for Drug Evaluation of China National Medical Products Administration website (NMPA) and ClinicalTrials.gov, a list and detailed information of cancer vaccine trials in China and the USA were acquired, respectively. Vaccines licensed for use in China and the USA were acquired from NMPA and Food and Drug Administration (FDA), respectively. Subgroup comparison in terms of initiated trials was conducted between the two countries.ResultsIn 2014-2024, there were 89 trials and 757 trials of cancer vaccine registered in China and the USA, respectively. In terms of the phase distribution, there were less phase I (28.1% vs 52.1%), phase II (15.7% vs 36.3%), and more phase III (40.5% vs 7.9%), phase IV (15.7% vs 3.7%) trials in China compared with those in the USA (χ2 = 116.58, P < 0.001). Regarding the trial scope, the proportion of global trials was significantly lower in China than that in the USA (2.2% vs 47.6%, χ2 = 66.78, P < 0.001). A significantly higher contribution rate was made by the top 20 pharmaceutical companies in China than that in the USA (16.9% vs 3.0%, χ2 = 35.43, P < 0.001). The numbers of trial status on open, completed and suspended in China are more than those in the USA (56.2%, 41.6%, 1.1% vs 43.6, 29.9%, 0.7%), while terminated trial is less than that in the USA (1.1% vs 9.1%). 5 cancer types were identified in China while there were more than 20 cancer types in the USA. Six cancer vaccines were approved in China while one was approved in the USA. With respect to indications, one cancer type was covered by the approved vaccines in China, which was fewer than the number of cancer types covered by the approved vaccines in the USA.ConclusionBoth China and the USA have made great progress in cancer vaccines in 2014-2024. The difference and gap between China and the USA highlight that more efforts should be paid on innovative cancer vaccines in China. Perhaps in the future, we can pay more attention to increasing the investment in drug research and development, carrying out more global multi-center clinical trials and participating more in trials led by top 20 pharmaceutical companies worldwide.